The comparison of bone mineral density of femoral head between non-hip fracture side and hip fracture side - Li, Xianlong (Sci Rep, 2020)
We aimed to analyze the associations of bone mineral density (BMD) of femoral heads, age and gender, and compare the differences in BMD between fracture side and non-fracture side by “3D Spine Exam Analysis” module in QCT Pro software. In this study, we identified patients who had undergone quantitative computed tomography (QCT) examinations between March 2016 and July 2018 and measured their trabecular volumetric BMD (vBMD) of femoral heads. This retrospective study enrolled 367 subjects. A total of 149 participants with images were randomly selected to verify the repeatability of this method. The relationship among the vBMD, age and gender was analyzed (n = 367), and the difference of vBMD between non-fracture side and fracture side were studied in subjects (n = 75) with low-energy hip fracture on one side and compared the image quality of bilateral hip joints. The intraclass correlation coefficients (ICCs) between the results measured by 2 operators and the results measured by the same operator showed excellent agreement (ICCs > 0.9). Multivariate regression equation of vBMD of femoral head, age and gender showed statistical significance (P < 0.05). vBMD showed negative correlation with age (P < 0.05), and showed no statistically significant relation with gender (P > 0.05). vBMD of non-fracture side was higher than that of fracture side, but the difference was statistically significant only at the middle layer (P(middle) < 0.05). In conclusions, the vBMD of femoral head as measured by "3D Spine Exam Analysis" module in QCT Pro software showed good repeatability. The trabecular vBMD of femoral head was negatively correlated with age, and not related with gender. The vBMD of femoral head was higher on non-fracture side than that on the fracture side.